A Review Paper on Big Data and Data Mining Concepts and Techniques - Prasdika Prasdika; Bambang Sugiantoro (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2018)
In the digital era like today the growth of data in the database is very rapid, all things related to technology have a large contribution to data growth as well as social media, financial technology and scientific data. Therefore, topics such as big data and data mining are topics that are often discussed. Data mining is a method of extracting information through from big data to produce an information pattern or data anomaly